PENGARUH PERSENTASE KOMPOSIT BATU APUNG DAN PLASTIK PET TERHADAP DAYA SERAP BUNYI - Izzuddin Abu Bakar; Sopyan Ali Rohman; Dedy Dharmawansyah; Fadhli Dzil Ikram (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
This sound absorption test was conducted by finding the value of Sound Transmission Class (STC) using the impedance tube testing method that refers to the ASTM E413 standard. This study aims to determine the effect of the percentage of composite pumice - PET plastic on sound absorption. As for the variation of the volume fraction of pumice: PET plastic that is (40:60, 50:50, 60:40)% based on the volume ratio. In this study it can be seen that the highest value in the sound absorption test is found in composites with a volume fraction of 40:60 with an STC value of 25, while the lowest value is found in composites with a volume fraction of 60:40 with an STC value of 11. Based on the results of this study, composite with a volume fraction of 40:60 is the best percentage in the sound absorption test because the greater the STC of a material, the better it is at absorbing sound.